The Restructuring and Privatization of the U.K. Electricity Supply-Was It Worth It? - Newbery, David M.; Pollitt, Michael G. (World Bank, Washington, DC, 2012)
The electricity supply industry in England and Wales was under public ownership from 1948 to 1990. For most of this period, the Central Electricity Generating Board (CEGB) operated all generation and transmission as a vertically integrated statutory monopoly. In 1990, the CEGB was restructured and privatized. This Note describes how a social cost-benefit analysis is conducted to assess the worthiness of the exercise and reports the results. The analysis shows that the effort was worth it. But there are two areas for improvement in the process of the restructuring and privatization. First, about a quarter of the net gains were transferred out of the country. If more attention had been paid to this possibility at the time of restructuring, some arrangement could probably have been found to prevent it. Second, introducing more competition in generation would have reduced excess entry and lowered prices, improving the distribution of the net benefits and increasing social welfare.